2019
DOI: 10.1111/puar.13034
|View full text |Cite
|
Sign up to set email alerts
|

How Do Intrinsic Motivations, Work‐Related Opportunities, and Well‐Being Shape Bureaucratic Corruptibility?

Abstract: A large body of research focuses on the institutional factors that shape country‐level corruption and the effectiveness of macro‐level anticorruption measures; however, corruption at the individual level remains understudied and thus poorly understood. This article examines the underlying causes of and mechanisms through which individual government bureaucrats engage in corruption. The researchers develop a framework that incorporates intrinsic motivations, work‐related opportunities, and work‐related well‐bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 81 publications
(160 reference statements)
0
20
0
Order By: Relevance
“…They proposed a conceptual framework and tested the relationship among these variables by a survey containing more than 1300 workers. The results showed that intrinsic motivation and well-being had direct coefficients on corruptibility [26]. Moreover, Graves and Sarkis [14] focused on employees' pro-environmental behaviors (PEBs) to explore the factors by leadership and motivation theories.…”
Section: Self-determination Theorymentioning
confidence: 99%
“…They proposed a conceptual framework and tested the relationship among these variables by a survey containing more than 1300 workers. The results showed that intrinsic motivation and well-being had direct coefficients on corruptibility [26]. Moreover, Graves and Sarkis [14] focused on employees' pro-environmental behaviors (PEBs) to explore the factors by leadership and motivation theories.…”
Section: Self-determination Theorymentioning
confidence: 99%
“…Jancsics's () article provides an innovative conceptual framework to classify corruption types and anticorruption tools to match the two for more desirable policy outcomes. Three articles in the symposium pay close attention to the propensity of individuals to engage in corruption, with Ni and Su () focusing on ordinary citizens, Zhang et al () on low‐level public employees, and Silitonga et al () on senior‐level civil servants. Araral et al’s () article also explains the proclivity for corruption at the micro level, but they use firms as the units of analysis.…”
Section: The Theme Of the Symposiummentioning
confidence: 99%
“… 3. Zhang et al (): “How Do Intrinsic Motivations, Work‐Related Opportunities, and Well‐Being Shape Bureaucratic Corruptibility?”…”
Section: Articles In the Symposiummentioning
confidence: 99%
“…From the literature (Gorsira, 2017a;Zhang et al, 2019) we learn that intrinsic motivation, a candidate's personal norms, is a significant indication of behaviour. This issue is not addressed in the cited international or national legal instruments.…”
Section: Intrinsic Motivationmentioning
confidence: 99%
“…Corruption is the work of individuals or groups of individuals. Their conduct is determined by intrinsic values, motivation, opportunities and inhibiting factors (Gorsira et al, 2018;Graycar & Prenzler, 2013;Zhang et al, 2019). Organisational human resources policies are powerful tools to shape these determinants, and while many influences are outside of the employer's reach to change (upbringing, environment, determining life events) their effects can be observed through monitoring, tests and screenings.…”
Section: Introductionmentioning
confidence: 99%